Physiology and physiological assessment of figure skating - Vescovi, J. D.; VanHeest, J. L. (The science of figure skating, 2018)
The sport of figure skating is governed by the International Skating Union (ISU) and consists of three disciplines: singles (ladies and men), pairs and ice-dance, each performing a short and free (long) program for international competitions. In general, singles skaters perform several types of jumps and spins during their programs, whereas pairs skaters also perform specific types of lifts, throws, spins and jumps. Ice-dance represents greater demands on technical aspects ( e.g., edgework) and coordination (e.g., twizzles) between the two skaters, and does not allow any jumps, spins or lifts in the programs. The energetics of figure skating have not yet been directly assessed; however, insights can be gained from other sports that are performed at similar intensities and durations. The cardiometabolic responses of high-level 800- to 1,500-meter male and female runners are reasonably similar to the short and free programs; thus, the estimated energy system contributions provide the best approximation of the energetics for figure skating. In light of the dominance of the aerobic energy system, muscle metabolite concentrations of phosphocreatine were reduced by more than 50% and creatine was nearly doubled after 1,500-meter running, highlighting the substantial contribution from the anaerobic energy system during events lasting 4-5 minutes. Nevertheless, the balance shifts from largely anaerobic to predominantly aerobic energy supply between 30 and 40 seconds in both running distances, and thus similar attributes would be expected in figure skating. The acute physiological responses to figure skating are similar to observed responses to middle-distance running and long-track speed skating for events of comparable duration.